2022
DOI: 10.1111/opn.12467
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between hospitalised older people’s fear of falling and adaptation to old age, quality of life, anxiety and depression

Abstract: Background Fear of falling affects older people physically and psychosocially, causing a decrease in their daily activities. Objectives The aim of this study was to determine the relationship between fear of falling (FoF) in hospitalised older people and their difficulty in adapting to old age, quality of life, anxiety, depression and other associated factors. Methods This descriptive correlational study was carried out in a university hospital. The sample consisted of 409 hospitalised older patients. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Limited studies have focused on the association between FOF, anxiety, and depression among older people. A previous study on this topic involved hospitalised older people, with significant associations found between anxiety, depression, and FOF (Turhan Damar & Demir Barutcu, 2022). The same significant associations were also found among married older people living in the community (Rakhshani et al, 2019).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Limited studies have focused on the association between FOF, anxiety, and depression among older people. A previous study on this topic involved hospitalised older people, with significant associations found between anxiety, depression, and FOF (Turhan Damar & Demir Barutcu, 2022). The same significant associations were also found among married older people living in the community (Rakhshani et al, 2019).…”
Section: Introductionmentioning
confidence: 79%
“…Older people who have experienced falls might develop a sequence of fear of falling (FOF), which has been categorised as a psychological and behavioural phenomenon commonly associated with older people (Pena et al, 2019;Turhan Damar & Demir Barutcu, 2022). FOF is defined as a cautious concern about falling that ultimately results in activities associated with daily life being restricted (Drummond et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…(1) Age <60 years old, (2) unable to walk independently, (3) unable to understand and accurately cooperate with the examination, (4) abnormal hearing and vision, (5) in the acute attack of heart, brain, lung and kidney diseases, (6) with de nite anxiety, depression and other psychological disorders or SAS and/or SDS score ≥50.…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…Changes in physical function and mental state are both factors that in uence falls. More and more studies have found that the mental state of the elderly will change once a fall occurs [5][6], followed by fear of falling and even anxiety and depression [7].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in physical function and mental state are both factors that influence falls. More and more studies have found that the mental state of the elderly changes once they experience a fall [5,6]. This is often followed by a fear of falling, and in some cases, even anxiety and depression [7].…”
Section: Introductionmentioning
confidence: 99%